Penilaian Ancaman Akibat Rokok dan Intensi Merokok pada Remaja - Maurida, Nurul; Putri, Prestasi Anita; Novitasari, Firda; Rosalini, Wike (FORIKES, 2022)
Smoking is a behavior that can cause health problems. Smoking behavior is generally first done in adolescence. This study aims to analyze the relationship between smoking threat assessment and smoking intention in adolescents. The design of this study was cross-sectional. The research subjects were 80 adolescents who were selected by simple random sampling technique. Data were collected through filling out a questionnaire developed from the Protection Motivation Theory (PMT). Data were analyzed using Spearman's rank test. The results showed that 54% of adolescents had a threat assessment due to smoking in the good category. As many as 65% of adolescents have the intention to not smoke. The value of p = 0.000 which indicates a relationship between the assessment of the threat caused by smoking with smoking intention. Assessment of the threat caused by smoking can be improved by increasing the knowledge of adolescents about the dangers of smoking.Keywords: threat assessment; intention; smoke; adolescentsABSTRAK Merokok merupakan perilaku yang dapat menimbulkan gangguan kesehatan. Perilaku merokok umumnya pertama kali dilakukan pada masa remaja. Penelitian ini bertujuan untuk menganalisis hubungan antara penilaian ancaman akibat rokok dengan intensi merokok pada remaja. Desain penelitian ini adalah cross-sectional. Subyek penelitian adalah 80 remaja yang dipilih dengan teknik simple random sampling. Data dikumpulkan melalui pengisian kuesioner yang dikembangkan dari Protection Motivation Theory (PMT). Data dianalisis menggunakan uji Spearman rank. Hasil penelitian menunjukkan bahwa 54% remaja memiliki penilaian ancaman akibat rokok dalam kategori baik. Sebanyak 65% remaja memiliki intensi untuk tidak merokok. Nilai p = 0,000 yang menunjukkan adanya hubungan antara penilaian ancaman akibat rokok dengan intensi merokok. Penilaian ancaman akibat rokok dapat ditingkatkan dengan meningkatkan pengetahuan remaja tentang bahaya merokok.Kata kunci: penilaian ancaman; intensi; merokok; remaja